CALIBRATED SULFUR ISOTOPE ABUNDANCE RATIOS OF THREE IAEA SULFUR ISOTOPE REFERENCE MATERIALS AND V-CDT WITH A REASSESSMENT OF THE ATOMIC WEIGHT OF SULFUR - Ding T.; Valkiers S.; Kipphardt H.; De Bievre P.; Taylor P.D.P.; Gonfiantini R.; Krouse R. (My University, 2001)
Calibrated values have been obtained for sulfur isotope abundance ratios of sulfur isotope reference materials distributed by the IAEA (Vienna). For the calibration of the measurements, a set of synthetic isotope mixtures were prepared gravimetrically from high purity Ag2S materials enriched in32S, 33S, and 34S. All materials were converted into SF6 gas and subsequently, their sulfur isotope ratios were measured on the SF5+ species using a special gas source mass spectrometer equipped with a molecular flow inlet system (IRMM's Avogadro II amount comparator). Values for the 32S/34S abundance ratios are 22.650 4(20), 22.142 4(20), and 23.393 3(17) for IAEA-S-1, IAEA-S-2, and IAEA-S-3, respectively. The calculated 32S/34S abundance ratio for V-CDT is 22.643 6(20), which is very close to the calibrated ratio obtained by Ding et al. (1999). In this way, the zero point of the VCDT scale is anchored firmly to the international system of units SI. The 32S/33S abundance ratios are 126.942(47), 125.473(55), 129.072(32), and 126.948(47) for IAEA-S-1, IAEA-S-2, IAEA-S-3, and V-CDT, respectively. In this way, the linearity of the V-CDT scale is improved over this range. The values of the sulfur molar mass for IAEA-S-1 and V-CDT were calculated to be 32.063 877(56) and 32.063 911(56), respectively, the values with the smallest combined uncertainty ever reported for the sulfur molar masses (atomic weights).